2011
DOI: 10.4028/www.scientific.net/amr.367.517
|View full text |Cite
|
Sign up to set email alerts
|

An Indirect Passive Solar Dryer for Drying

Abstract: A solar drying system designed on the principles of convective heat flow, constructed from local materials was employed in drying yam (Dioscorea Alata). A glass collector having an efficiency of about 0.63 was used along with an absorber for absorbing the heat energy. The drying chamber consisted of drying trays. A chimney fitted at the top centre of the drying chamber enhanced airflow. Air passing through the collector heated up and dried the foodstuff in the drying chamber. The latitude of Ilorin is 8.26oN a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
(2 reference statements)
1
8
0
Order By: Relevance
“…The following criteria were considered in the design of the solar dryer (Basunia and Abe, 2001; Alonge and Oniya, 2011): (i) quantity of product to be dried -1 kg of cassava chips per batch; (ii) initial moisture content of product -70% (wb);(iii) final moisture content of product -12% (wb); (iv) average temperature and relative humidity of Ilorin -27 o C and 70% respectively; and (v) useful sunshine hour in Ilorin -9.00h to 17.00h Nigeria time (Alonge and Hameed, 2007;Alonge and Oniya, 2011, A5); (vi) the actuator jack to be regulated by a timer in such a way that it will move at an interval of 1 hour; and (vii) power required to activate the actuator jack and sensor.…”
Section: Design Considerationsmentioning
confidence: 99%
“…The following criteria were considered in the design of the solar dryer (Basunia and Abe, 2001; Alonge and Oniya, 2011): (i) quantity of product to be dried -1 kg of cassava chips per batch; (ii) initial moisture content of product -70% (wb);(iii) final moisture content of product -12% (wb); (iv) average temperature and relative humidity of Ilorin -27 o C and 70% respectively; and (v) useful sunshine hour in Ilorin -9.00h to 17.00h Nigeria time (Alonge and Hameed, 2007;Alonge and Oniya, 2011, A5); (vi) the actuator jack to be regulated by a timer in such a way that it will move at an interval of 1 hour; and (vii) power required to activate the actuator jack and sensor.…”
Section: Design Considerationsmentioning
confidence: 99%
“…The amount of water to be removed from crops r m ( kg ) can be calculated as [20][21] ( ) Where, is the initial mass of wet sample; while and are the initial fraction and final fraction of moisture contents. The moisture content on wet basis ( ) and on dry basis ( ) are given by [22][23]:…”
Section: Theoretical Framework 21 Useful Energy Required For Drying mentioning
confidence: 99%
“…A solar drying system based on the principles of convective heat flow, with use of local materials for yam chip was designed by Alonge et. al [6]. It was observed that the drying time was reduced from 52 hours for sun drying to 45 hours for solar drying of yam chip.…”
Section: Introductionmentioning
confidence: 98%